Interculturality and intercultural curriculum for higher education in México (Revista Electrónica Calidad en la Educación Superior, 2019)
In this article, the concept of interculturality is exposed, as well as its importance at present in order to move towards the construction of an intercultural nation, it is taken up and analyzed as the first point towards this purpose, the way in which intercultural universities are implemented in Mexico and its educational model, based on this, an intercultural curriculum proposal for higher education institutions that responds to the social and cultural contexts of where they are located is outlined. Finally, it is stated that education must respond to the social needs and demands of different cultural groups
Keywords: interculturality, intercultural education, culture, curriculum